'Your skin has to be elastic': the politics of belonging as a selected black academic at a 'transforming' South African university. Issue 2 (7th February 2022) - Belluigi, D. Z.; Thondhlana, G.
Abstract: A presumed indicator of change, in terms of the South African higher education sector's racialised past, are the quantitative measures of numerical 'diversity' within the academic staff composition at historically white institutions. To better inform policy, academic development curricula and institutional culture, this study focuses on macroaggressions related to the mis/recognition and un/belonging of black academics who were selected for prestigious affirmative 'accelerated development programmes' for transforming the academic staff composition. Insights and narratives elicited via report-and-respond questionnaires, reflective small group discussions and an arts-based method, indicated that participants (a) experienced various microaggressions as members of different communities within the institution, and as a result (b) negotiated different identities according to social group norms, affordances and settings. The study brings to the fore the complex social processes and agential consequences of negotiating the politics of belonging in the looming shadow of legacies of conflict and oppression.